2019
DOI: 10.2337/dc18-1226
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Elevated Blood Glucose Levels in 2017: Diagnosed and Undiagnosed Diabetes, Gestational Diabetes Mellitus, and Prediabetes

Abstract: This study was conducted to update national estimates of the economic burden of undiagnosed diabetes, prediabetes, and gestational diabetes mellitus (GDM) in the United States for year 2017 and provide state-level estimates. Combined with published estimates for diagnosed diabetes, these updated statistics provide a detailed picture of the economic costs associated with elevated blood glucose levels. RESEARCH DESIGN AND METHODS This study estimated medical expenditures exceeding levels occurring in the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
147
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(153 citation statements)
references
References 23 publications
0
147
0
6
Order By: Relevance
“…GDM only slightly raised medical costs for newborns (average US $40/newborn) but substantially raised the mother's costs related to the pregnancy and birth (average US $5760/mother). The breakdown for higher costs includes inpatient care (US $3140), prescription medicine (US $1200), ambulatory visits (US $1140), and emergency care (US $280) . The overall health and economic costs associated with unrecognized and untreated GDM will undoubtedly be several‐fold higher underscoring the importance of screening for and management of GDM.…”
Section: The Health Economic Argument For Focusing On Postpregnancy Carementioning
confidence: 99%
“…GDM only slightly raised medical costs for newborns (average US $40/newborn) but substantially raised the mother's costs related to the pregnancy and birth (average US $5760/mother). The breakdown for higher costs includes inpatient care (US $3140), prescription medicine (US $1200), ambulatory visits (US $1140), and emergency care (US $280) . The overall health and economic costs associated with unrecognized and untreated GDM will undoubtedly be several‐fold higher underscoring the importance of screening for and management of GDM.…”
Section: The Health Economic Argument For Focusing On Postpregnancy Carementioning
confidence: 99%
“…3 Individuals with prediabetes may exhibit poorer health and incur increased medical expenditures compared to those without prediabetes because of greater use of health care services, medications, and other health care products. 5 Annual per capita health care spending was roughly $2700 more for those who had transitioned from prediabetes to diabetes among a commercially insured adult popuation. 6 The economic costs of diabetes can be mitigated by participation in lifestyle change programs (LCPs), which are shown to successfully prevent or delay the onset of diabetes among their participants, such as those offered through the Centers for Disease Control and Prevention (CDC)-led National Diabetes Prevention Program.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic diseases, such as diabetes and obesity, are estimated to have an annual global economic impact in the trillions of (US) dollars (16)(17)(18)(19)(20). The therapeutic value of the recently developed glutides and gliptins highlights the benefits of pharmacological agents that augment glucose stimulated insulin secretion (GSIS) (21).…”
Section: Introductionmentioning
confidence: 99%
“…The SNAP25 Δ3/Δ3 mouse has demonstrated the importance of the Gβγ-SNARE pathway in a number of neurological processes, including stress and pain processing, as well as long-term potentiation (6) and spatial memory (5). We hypothesized that the SNAP25 Δ3/Δ3 mouse may have an altered metabolic phenotype because neurological processes use SNAREdependent signals to regulate a number of metabolically important processes, such as feeding behavior, energy balance, and thermoregulation (7-12), and the secretion of important metabolic hormones, such as insulin (13)(14)(15).Metabolic diseases, such as diabetes and obesity, are estimated to have an annual global economic impact in the trillions of (US) dollars (16)(17)(18)(19)(20). The therapeutic value of the recently developed glutides and gliptins highlights the benefits of pharmacological agents that augment glucose stimulated insulin secretion (GSIS) (21).We hypothesized that the SNAP25Δ3 mutation would similarly enhance GSIS because previous studies have indicated that norepinephrine inhibits insulin exocytosis via the α2A adrenergic receptor (AR) through Gβγ inhibition of SNARE in the pancreatic β-cell (22).…”
mentioning
confidence: 99%